2020
DOI: 10.4103/jfmpc.jfmpc_498_20
|View full text |Cite
|
Sign up to set email alerts
|

Why social accountability of medical schools in Sudan can lead to better primary healthcare and excellence in medical education?

Abstract: Introduction: Medical education in Sudan continues to evolve and progress with proliferation in the number of medical schools after 1990. Social factors and the geographical location of Sudan will increase the opportunity of success of medical schools to be socially accountable. In this analysis, we explained why social accountability is needed in Sudan and how this can enhance both excellence in medical education and primary health care, especially in rural areas. Methodology: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Each college in the university has a student club, including a social team responsible for educating and raising the community's health awareness through campaigns. Prioritizing the research based on the population's needs is one of the ways that can successfully improve SA of an institution (Strasser et al, 2013;Ahmed et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each college in the university has a student club, including a social team responsible for educating and raising the community's health awareness through campaigns. Prioritizing the research based on the population's needs is one of the ways that can successfully improve SA of an institution (Strasser et al, 2013;Ahmed et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, other countries like Sudan, Saudi Arabia, and Egypt have also taken initiatives toward achieving community-based, socially accountable medical education. A study that assessed the SA of the Faculty of Medicine at the University of Gezira (FMUG), Sudan, concluded their educational program as socially responsible and socially accountable only in certain aspects (Ahmed et al, 2020). Hosny et al (2015) suggested using the conceptualization production usability (CPU) model to assess SA in medical institutions.…”
Section: Introductionmentioning
confidence: 99%
“… 46 Among the enabling factors are accreditation, leadership, a formal SA structure in medical schools, the support of champions, 14 and the formation of alliances. 47 Furthermore, the studies’ examination revealed that the highest number of publications came from Iran, which has the largest number of medical schools in the region. 13 Factors that might have been crucial to the broader spread of SA in Iran include its integration of medical education into the health system and its inclusion of supervised community-related activities in medical education.…”
Section: Discussionmentioning
confidence: 99%
“… 13 Factors that might have been crucial to the broader spread of SA in Iran include its integration of medical education into the health system and its inclusion of supervised community-related activities in medical education. 48 Additionally, collaboration and alliances between different medical schools are especially important, 47 however, the review showed that most of the articles reflected work from a single medical school and only a few were from two or more medical schools; two of the articles from Sudan were produced by a consortium of international medical schools that worked jointly on SA. 37 …”
Section: Discussionmentioning
confidence: 99%
“…Increased focus has also been devoted to the accountability of medical schools to review their approaches to learning and assessment. Specifically, approaches to learning and assessment are evaluated in terms of their response to population needs and their ability to ensure the development of health professionals with relevant competencies to support the evolutions in health systems [4][5][6]. Today, scholars and educationalists see medical education as a continuum increasingly referred to as lifelong learning, from undergraduate medical education (UME) to graduate medical education (GME) and continuing medical education (CME) or continuing professional development (CPD) [7,8].…”
Section: Introductionmentioning
confidence: 99%